Media vs public trust during the pandemic - Diyah Indiyati; Siti Chotijah; Hartin Nur Khusnia; Muhlis Muhlis (Universitas Mataram, 2020)
The pandemic puts mass media on the main stage in the public spotlight. In the midst of rampant misinformation and disinformation related to the Corona Virus Disease 2019 (Covid-19) pandemic, the public's expectations for truthfull information are often wrapped in bubbles that make the public even more confused as to which media to trust. Meanwhile, the main role of the mass media, whichis expected to be able to increase public awareness of the pandemic that has occurred, actually leads to a point of view that questioned media trust. This paper analyzes the things that affect public confidence in the media during a pandemic.Keyword: Media, public trust, pandemic